2006
DOI: 10.1086/506004
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ambient Temperature and the Energy and Protein Content of Food on Nitrogenous Excretion in the Egyptian Fruit Bat (Rousettus aegyptiacus)

Abstract: The diets of frugivorous and nectarivorous vertebrates contain much water and generally have high energy but low protein contents. Therefore, we tested the prediction that to save energy under conditions of high energy demands and high water intake, frugivorous Egyptian fruit bats (Rousettus aegyptiacus) will increase both the absolute quantity and the proportion of ammonia in their urine. We also examined whether such changes occur when protein intake is low and water intake is high. We did three feeding tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Previous studies have shown a modest increase in ammonia excretion in urine when energy demands of bats were increased by lowering ambient temperature (Korine et al, 2006) or at low N intake (Herrera M. et al, 2006). Our study showed a large increase in ammonia excretion and a switch to ammonotely in some of the bats when energy ingestion was constrained and N intake was high.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Previous studies have shown a modest increase in ammonia excretion in urine when energy demands of bats were increased by lowering ambient temperature (Korine et al, 2006) or at low N intake (Herrera M. et al, 2006). Our study showed a large increase in ammonia excretion and a switch to ammonotely in some of the bats when energy ingestion was constrained and N intake was high.…”
Section: Discussionsupporting
confidence: 55%
“…We used the x-intercept of the linear regression equation for bats on sugar-rich diets to estimate apparent maintenance N requirements. Korine et al (Korine et al, 2006) assumed that the cost of synthesizing 1molof urea was 5mol of ATP, and estimated that R. aegyptiacus saved 2% of its daily water; closed symbols). Regression lines are shown only when there were significant correlations after multiple regression analysis followed by partial correlation estimates (r p ).…”
Section: Forms Of N Excretionmentioning
confidence: 99%
See 3 more Smart Citations